Analisis Efisiensi Penyaluran Air Irigasi pada Saluran Sekunder di Areal Persawahan Desa Kolongan Kecamatan Kalawat Kabupaten Minahasa Utara - Tadung, Sri Wanni Jumiati; Tooy, Dedie; Rantung, Ruland A. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
Agriculture is a strategic sector that plays a crucial role in ensuring national food security, particularly in rural areas where the majority of the population depends on farming activities for their livelihood. One of the key factors determining the success of farming, especially rice cultivation, is the availability of sufficient, equitable, and timely irrigation water throughout the growing season. In this regard, irrigation systems serve as vital infrastructure supporting agricultural sustainability. This study aims to calculate the efficiency of water distribution based on channel capacity and the ratio of upstream-downstream water discharge, as well as to calculate the value of water loss due to technical and non-technical factors. The results indicate that the effective efficiency of the irrigation channels is 66% for Channel 1 and 74% for Channel 2. Overall, these efficiency levels are still considered relatively low. Water losses occurred in both channels, totaling 0.02678 m³/s for Channel 1 and 0.01423 m³/s for Channel 2. These losses were attributed to seepage, percolation, evaporation, and direct water withdrawal by farmers at several points, which was exacerbated by the absence of an active water management institution for the irrigation channels.